Tactile poetics : touch and contemporary writing - Jackson, Sarah, 1977- (Edinburgh University Press, 2015)
The intimate links between the page and the skin have been explored by writers for centuries. Yet despite the current interest in the surface of the body, the relationship between touching and writing remains neglected. Drawing on new debates in deconstruction and psychoanalysis, this book provides an original and timely intervention in the field. Exploring insights from Jacques Derrida and HÃ♭lÃ·ne Cixous, and through close readings of work by writers such as Anne Carson, Siri Hustvedt and Michael Ondaatje, Tactile Poetics investigates the law of tact that always interrupts contact, and examines the different ways that literary texts work to 'touch' their readers. Key Features Conceptualises the relationship between touching and writing through a theory of 'tactile poetics' Offers in-depth analysis of a range of literary genres including short fiction, poetry, autobiography, correspondence and the novel Examines writings on touch by Anzieu, Cixous, Derrida, Freud and Nancy Explores the intersections between creative and critical thinking and writing